Copper oxide nanoparticles-loaded zeolite and its characteristics and antibacterial activities - A. Alswat, Abdullah; Ahmad @ Ayob, Mansor; Hussein, Mohd Zobir; Ibrahim, Nor Azowa; A. Saleh, Tawfik (The Chinese Society for Metals, 2017)
In the present work, a simple and green co-precipitation method was used to prepare copper oxide-zeolite nanocomposites (CuO-zeolite NCs). The weight ratio (1, 3, 5, 8 and 10 wt%) of CuO nanoparticles (NPs) loaded into zeolite was investigated to obtain the optimum CuO distribution for antibacterial activities. The prepared CuO-zeolite NCs were characterized by ultraviolet-visible (UV–vis) spectroscopy, Fourier transform infrared (FT-IR) spectroscopy, powder X-ray diffraction (XRD), and energy dispersive X-ray fluorescence spectrometry (EDXRF). The transmission electron microscopy (TEM) and field emission scanning electron microscopy (FE-SEM) revealed a uniform surface morphology of the CuO-zeolite NCs. The UV–vis spectrum of NCs showed absorption peaks between 230 and 280 nm for nano-CuO in the XRD patterns, and new peaks appeared between (36.56°–38.83°) related to the CuO. At weight ratio less than 10 wt%, the CuO nanoparticles loaded to the zeolite exhibited spherical shapes with average particle diameter of 6.5 nm measured by TEM and XRD. Antibacterial activities were tested against Gram-negative and Gram-positive bacteria. The obtained results showed that, CuO-zeolite NCs with 8 wt% CuO nanoparticles had the highest antibacterial activities against Bacillus Subtilis B29 and Salmonella Choleraesuis ATCC 10708, which can be attributed to the good dispersion of CuO NPs on the zeolite surface.